Spectrum of congenital mitral valve abnormalities associated with solitary undifferentiated papillary muscle in adults - Mohan, Jagdish C. (Indian Heart J, 2016)
BACKGROUND: Congenital anomaly wherein the mitral valve leaflets are directly attached to the papillary muscle(s) (PM) with or without short under-developed chords is rarely reported in adults. Patients with two PMs with an intervening fibrous bridge have also been included under this head in previous studies. METHODS: Echocardiography enables accurate evaluation of the morphology and function of valve leaflets, chordae tendineae, and PM. This report describes a series of six patients aged 56–84 years who had abnormal mitral valve with a large solitary and anomalously inserted PM seen over a period of 3 years. Only those patients who had a single pillar or bridge-like PM and either absent tendinous chords or small under-developed chords were included in the analysis. RESULTS: Among 9600 consecutive echocardiograms performed, six patients met the criteria of an abnormal mitral valve with solitary large PM. Two patients underwent mitral valve replacement with partial excision of the PM wherein echocardiographic observations were confirmed. The patients were previously followed with the diagnosis of hypertrophic cardiomyopathy (3) and rheumatic mitral valve disease (3). Multi-planar reconstruction of 3D echocardiographic images provided incremental value in assessing the detailed patho-anatomy of PMs in these cases. CONCLUSION: In adult patients, a high index of suspicion is required to detect congenital mitral stenosis/regurgitation with large solitary PM (resembling a parachute mitral valve) which may masquerade as hypertrophic cardiomyopathy or rheumatic mitral valve disease.